2014
DOI: 10.4028/www.scientific.net/msf.783-786.2491
|View full text |Cite
|
Sign up to set email alerts
|

Development of Nickel Based Superalloys for Advanced Turbine Engines

Abstract: Superalloys have been developed for specific, dedicated properties and applications. One of the main application for this material is advanced, high-performance aircraft engines elements. Turbine engine creates harsh environments for materials due to the high operating temperature and stress level. Hence, as described in this article, many alloys used in the turbine section of these engines are very complex and highly optimized. This article provides an overview of structural changes that occur during the agin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 2 publications
(3 reference statements)
0
5
0
1
Order By: Relevance
“…Zastosowanie tych metod pozwala na wyprodukowanie, w oparciu o trójwymiarowy model komputerowy (Computer Aided Design -CAD), komponentów silnika lotniczego o złożonej geometrii, które ze względu na skomplikowaną geometrię nie są łatwe do wytworzenia innymi metodami [1,2,3]. Techniki wytwarzania RP oraz RM znacząco przyspieszają procesy pozyskiwania nowych oraz rozwijania dotychczas stosowanych rozwiązań technologicznych.…”
Section: Wstępunclassified
“…Zastosowanie tych metod pozwala na wyprodukowanie, w oparciu o trójwymiarowy model komputerowy (Computer Aided Design -CAD), komponentów silnika lotniczego o złożonej geometrii, które ze względu na skomplikowaną geometrię nie są łatwe do wytworzenia innymi metodami [1,2,3]. Techniki wytwarzania RP oraz RM znacząco przyspieszają procesy pozyskiwania nowych oraz rozwijania dotychczas stosowanych rozwiązań technologicznych.…”
Section: Wstępunclassified
“…Nickel-chromium based UNS N06003 is an alloy with advantage of solid solution strengthening mechanism and precipitation hardening mechanism. This is the primary cause for its high temperature resistance [5,6]. This alloy is also known as ASTM 80Ni-20Cr, EN NiCr8020 and NICHOME V [7].It forms a preventive layer of chromium oxides on its surface in severe conditions [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The macroscopic structure was cubic, and the strengthening phase was surrounded by continuous solid solvent matrix phase, which presented a chessboard-like compact and regular arrangement [2]. It has been found that the basic characteristics of the strengthened phase, such as shape, size, distribution, and volume fraction, have an important effect on the mechanical properties of superalloys [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%